Amīna and the Breaking of the Secular Silence: Revisiting The Cairo Trilogy by Naguib Mahfouz - Kundos, Zahiye (Political theology, 2024)
Following critiques of secularism, feminist theory and literary analysis, this article revisits the much interpreted yet never exhausted Arabic masterpiece, the Cairo Trilogy (1956–1957), by Nobel laureate Naguib Mahfouz (1911–2006). The Cairo Trilogy depicts the lives of the middle-class ʿAbd al-Jawād family in colonial Cairo during the interwar period amidst the process of modernization and national uprising against British colonial domination. Scholars have considered the relations in the Jawādī family through a patriarchal lens via the perspective of the son Kamāl, the protagonist who represents the secular Arab intellectual. This study, instead, follows Amīna, the mother of the family, and her relationship to her two sons, Kamāl and Fahmy, to explore the different options and various relations between the religious and the secular in this colonial context. By reading the Jawādī family this way, this article uncovers the orientalist-secular construction of religion and religious ways of resistance despite colonial disruptions.